Overconfidence and bailouts - Daniel Gietl (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
Empirical evidence suggests that managerial overconfidence and government guarantees contribute substantially to excessive risk-taking in the banking industry. This paper incorporates managerial overconfidence and limited bank liability into a principal-agent model, where the bank manager unobservably chooses effort and risk. An overconfident manager overestimates the returns to effort and risk. We find that managerial overconfidence necessitates an intervention into banker pay. This is due to the bank's exploitation of the manager's overvaluation of bonuses, which causes excessive risk-taking in equilibrium. Moreover, we show that the optimal bonus tax rises in overconfidence, if risk-shifting incentives are sufficiently large. Finally, the model indicates that overconfident managers are more likely to be found in banks with large government guarantees, low bonus taxes, and lax capital requirements.
Keywords: H20; H30; G28; G41; 330; Overconfidence; Bailouts; Banking Regulation; Bonus Taxes